2010
DOI: 10.4093/kdj.2010.34.4.237
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Adiponectin/Leptin Ratio with Homeostasis Model Assessment Insulin Resistance Index and Metabolic Syndrome in Apparently Healthy Korean Male Adults

Abstract: BackgroundWe investigated the relationships of adiponectin/leptin (A/L) ratio with cardiovascular risk factors, insulin resistance index, and metabolic syndrome (MS) in apparently healthy Korean male adults.MethodsSixty-eight male subjects were enrolled among the participants of an annual health check-up program (mean age, 55.1 years). Percent body fat (%) was measured using a bioelectric impedance analyzer. Serum leptin level was measured via radioimmunoassay, and adiponectin level was measured using an enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 21 publications
4
49
1
1
Order By: Relevance
“…It was reported that the A/L ratio gradually decreases with the number of MetS components (27). In addition, it is suggested that the A/L ratio is more effective in relevance as a parameter of insulin resistance compared with adiponectin or leptin alone, and a more sensitive and reliable marker of insulin resistance than HOMA-IR in patients with type 2 diabetes (28).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the A/L ratio gradually decreases with the number of MetS components (27). In addition, it is suggested that the A/L ratio is more effective in relevance as a parameter of insulin resistance compared with adiponectin or leptin alone, and a more sensitive and reliable marker of insulin resistance than HOMA-IR in patients with type 2 diabetes (28).…”
Section: Discussionmentioning
confidence: 99%
“…Уровень адипонектина снижается у лиц с ожирени-ем, а повышение его концентрации обладает ано-рексигенным эффектом и сопровождается сниже-нием массы тела [64]. Как адипонектин, так и леп-тин продуцируется жировой тканью и оказывает влияние на потребление пищи, инсулинорезистент-ность, а также липолиз [65,66]. В 32-недельном рандомизированном перекрест-ном исследовании изучалось влияние инсулина де-темир на потребление пищи и массу тела у пациен-тов с СД1 (n=23) [56].…”
Section: терапия детемиром и реакция гормонов регулирующих аппетитunclassified
“…67 Both adiponectin and leptin are derived from adipose tissue and they influence food intake, insulin resistance, and lipolysis. 68,69 Comparison of the effects of insulin detemir and human insulin on 3T3-L1 preadipocytes indicated that human insulin, but not insulin detemir, was associated with clonal expansion and that insulin detemir had reduced adipogenic effects versus human insulin. 70 Thus, while the mechanisms underlying lower weight gain with insulin detemir versus other insulins are not clear, it is reasonable to speculate that they may involve albumin binding, preferential activity in brain and liver, and favorable effects on adipocytes.…”
Section: Cns Influencesmentioning
confidence: 99%